Use of endoscopic band ligation alone and in combination with nonselective beta blockers for prevention of variceal bleeding in ascites patients on the liver transplant waiting list - V. L. Korobka; V. D. Pasetchnikov; R. V. Korobka; E. S. Pak; A. M. Shapovalov (Вестник трансплантологии и искусственных органов, 2022)
Objective: to conduct a comparative analysis of the effectiveness of two methods – endoscopic band ligation (EBL) alone and in combination with nonselective beta blockers (NSBB) – used for prevention of variceal bleeding (VB); to evaluate their impact on patient survival in severe ascites during long-term stay on the liver transplant waiting list (LTWL). Materials and methods. A retrospective comparative study of two groups of patients with decompensated liver disease, ascites and varices included in the LTWL, who received EBL (n = 41, group 1) and EBL + NSBB (n = 45, group 2). Results. The groups being compared did not differ in demographics, clinical parameters, MELD and Child–Turcotte–Pugh scores. There were no significant differences in the incidence of severe ascites, particularly diuretic-resistant ascites. The study groups did not differ in the incidence of mediumand large-sized varices. Incidence of bleeding did not differ in both groups. Overall mortality was significantly higher in the EBL + NSBB group than in the EBL group. Patient survival was lower, while mortality was higher in the EBL + NSBB group. The combined therapy group had a significantly higher number of acute kidney injury (AKI) than the EBL group. Conclusion. The compared methods are equivalently effective in preventing VB in patients with decompensated cirrhosis with a prolonged stay on the waiting list. Survival rate is significantly lower, while mortality is significantly higher in the EBL + NSBB group than in the EBL group.